Manajemen Pesantren untuk Membangun Kemandirian Santri Berbasis Kewirausahaan - Nur Alfi Mawaddah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
Islamic boarding schools play an important role not only in spiritual and academic development, but also in shaping the independence of students in facing the challenges of the times. One of the strategies used is through the management of entrepreneurship-based business units. This study aims to describe the management of Islamic boarding schools in optimising student independence through entrepreneurship and to explain the implications of this program on the development of students' skills, attitudes, and independence. The research uses a qualitative approach with a case study method at the Al-Urwatul Wutsqo Islamic Boarding School in Jombang. Data were collected through observation, interviews with caregivers, administrators (ibu nyai, head of business units), and students, as well as documentation. Data analysis included data reduction, data presentation, and verification. The study found that the pesantren management optimises the independence of santri through various business units such as cooperatives, furniture, fisheries, agriculture, computer training centres, and clothing/sewing. Santri are educated as warriors of the Qur'an who have a spirit of jihad, do not depend on rewards, and are equipped with entrepreneurial skills to be economically independent. As a result, the students' skills are increasingly honed, they do not depend on others, can manage their free time, have a sense of responsibility, and uphold their duties. The level of independence developed by the students covers emotional, behavioural, skill, and value aspects. Islamic boarding school management through entrepreneurship has proven to be effective.